Review of the cold atmospheric plasma technology application in food, disinfection, and textiles: A way forward for achieving circular economy - Reema,; Khanikar, Rakesh Ruchel; Bailung, Heremba; Sankaranarayanan, Kamatchi (Frontiers in Physics, 2022)
Cold atmospheric plasma (CAP) is a promising technology quite useful in many industries including biotechnology, biomedical, textiles and food processing. The contrivance of plasma technology can be a potential game-changer to use in any possible ways in these industries. This CAP technology is technically a green process with no generation of chemically harmful substances with more ecological and economic benefits. This review paper will focus on the research done in the textile industry and food processing, how plasma brings in an effective change in these industrial sectors as well as application of CAP in disinfection, sterilization, microbial inactivation, surface modification to obtain desirable results. Recently, there has been reports of successful use of CAP technology for surface inactivation of SARS-CoV-2, plasma activated water for disinfection of SARS-CoV-2. This article will streamline the innovations in textiles and food industries achieved using plasma technology and what gaps industries face while manufacturing. The focus will be on what research has already done while depicting the gaps and opportunities for using plasma technology in these industries and make use of it to achieve circular economy, which is one of the major policies of the European countries. Circular economy enables manufacture to produce such goods which can be reuse, recycle, refurbish, and repair rather than scrapping them after single use. The reduction of harmful chemicals, wastewater treatment, sterilization achieved using plasma technology and give opportunity to reuse the resources which consequently help to achieve most of the UN’s sustainable development goals and help society to live a sustainable and better life.